Fadjar 'Sopsan' Creativity in the Creation of Tembang Banyumasan - Nurul Aulia Dewi Arifin; Sunarto Sunarto; Suharto Suharto (Universitas Negeri Medan, 2023)
Artists and creativity are inseparable. Artists in creativity have the challenge of transforming an abstract idea into a practical one in order to create a good creation. Fadjar Praptono, a musician from Banyumas, creates based on the Encouragment of responses to enviromental situatons by paying attention to the suitability contents of the song lyrics with the existing social, political and cultural situations. This research discusses Fadjar's creative process in creating tembang Banyumasan that have a distinctive Banyumas character. This research uses a descriptive qualitative method that aims to understand the object studied in more depth. This research uses a case study design, which is focuses on exploration of finite system. The data collection techniques used are observation, interviews, and literacy studies. The interview was conducted directly with the main informant Fadjar 'Sopsan'. The study results prove that Fadjar went through several continuous stages in the creation of Banyumasan songs, including creative ideas, cultural knowledge, experience, work concepts, and creative act.